Diagnostic Related Groups (drgs): Resourceful tools for financial crisis times? (2011)
This document is intended to be read by the Colombian Ministry of Social Protection (former MoH) and includes some recommendations that could be implemented on the aim to increase allocative efficiency, thus improving macroeconomic performance of the Colombian Health System (CHS). It will be conducted as follows: first it will briefly review the background and actual context of the CHS, after this, will mention some related issues that justify a policy intervention on strategic purchasing to promote long run sustainability and hopefully the future attainment of major goals such as universal coverage and quality improvement. After prioritizing the main financial threats to the system, based on findings from literature review from countries that have successfully implemented similar policies, this paper will make some policy recommendations on regards especially to inpatient health care services in Colombia.